Pengembangan Bahan Ajar Berbasis Naskah Terjamahan Puspakarma pada Materi Karya Fiksi di SMP - Opi Putri Andiyanti; Aswandikari; Syaiful Musaddat (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This research is research and development. This research aims to develop teaching materials based on Puspakarma translated manuscripts as model texts for fiction work material in junior high schools, using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The stages followed in this research are analyzing the need for open materials; Designing teaching materials according to the curriculum and Permendikbud (2016) regarding textbooks used by educational units; develop open materials according to previously prepared plans; The teaching materials that have been developed are validated first by validators, then implemented in the learning process; and stream student learning outcomes after using the teaching materials that have been developed, as well as knowing student responses to the teaching materials developed through questionnaires filled out by students. The number of students who were research subjects and respondents in this study were 6 students consisting of 2 students with high, medium and low cognitive levels. The data collection techniques used were literature study, observation, interviews, questionnaires and tests. The instruments used were questionnaires for validity testing given to material expert validators, language expert validators, media expert validators, and one Indonesian language teacher at SMPN 6 Praya Timur, as well as response questionnaires given to students to find out students' assessments of the teaching materials. developed. The research results show that the total scores obtained from the validation results by the validators have an average of 4.76 and 4.12 based on student responses to the Puspakarma translation script-based teaching materials developed. These scores respectively fall into the ranges X>4.2 and 3.4<×≤4.2, which means the product has very good and good criteria. This can be concluded that the developed product is suitable to use.